Mineralogy and Geochemistry of Pleistocene Volcanics at Embagai Caldera and Natron Basin, Tanzania: Potential Constraints on the Stratigraphy of Olduvai Gorge - (:unkn) unknown (My University, 2014)
Olduvai Gorge is a paleoanthropologically significant site on the shoulder of the East African Rift Valley of north-central Tanzania, hosting Pleistocene-aged hominid fossils and stone tools. Several volcanoes in the adjacent Ngorongoro Volcanic Highlands (NVH) have erupted volcanic material into Olduvai and other nearby sedimentary basins. Embagai (Elanairobi) is a Pleistocene caldera within the NVH. It is a potential source volcano for Olduvai tuffs, particularly for Bed II and younger deposits, as it is consistent in overall composition (nephelinite and trachybasalt) and general age. Nephelinitic and phonolitic lava and tuff samples were collected from the caldera floor and the western, eastern, and northeastern sides of the caldera. Common primary minerals included nepheline, clinopyroxenes, titanomagnetite, and andradite garnets exclusive to alkaline volcanic settings. Secondary alteration significantly affected the quality of the geochemical and mineralogical results, with analcime, phillipsite, and calcite as the dominant secondary minerals. Unaffected samples plot as nephelinites. The compositions of phenocrysts of augite, feldspar, and titanomagnetite sampled from both Embagai and the Olduvai beds were compared. High-Mg augite compositions from the northern rim and western flank of Embagai are most similar to those of Olduvai Bed II. Feldspars are rare and distinctively K-rich in Embagai samples, which are dominated by nepheline compared to Olduvai tuffs. Overall, the mineral compositions and assemblage of Embagai appear to be a better match for a younger Olduvai Bed III tuff. The Pleistocene Peninj Group, exposed to the north of the NVH along the western margin of Lake Natron, is also paleoanthropologically important. It is comprised of the Humbu and Moinik Formations, which contain clastic sediments along with tephras and lavas likely associated with local eruptions from nearby volcanoes. The Main Tuff within the Humbu Formation is interlaid with the Wa Mbugu Basalt to the south of Peninj. This study compares the geochemistry and paleomagnetism of both well-constrained and unknown samples of the Wa Mbugu and other basaltic lavas in the vicinity to constrain the various units in this highly faulted and fragmented region. Samples were variably altered, with zeolites dominating the alteration assemblage. Geochemical results indicate that bulk major and minor elements alone are not enough to distinguish between some lavas of different stratigraphic positions but similar compositions, and would require further study using trace elements, phenocryst compositions, or other means. An oriented sample of the Wa Mbugu appears to indicate transitional polarity as opposed to the normal polarity commonly found with this unit. A second oriented lava sample had reversed polarity, however is not compositionally similar to the nearby Hajaro lava (reversed). This second lava may represent a previously undocumented flow. With further study of both Embagai and the Natron basin lavas focusing on phenocryst mineralogy in unaltered samples, additional correlations could lead to a higher resolution inter-basin stratigraphic framework for the NVH and for the surrounding paleontologically and archaeologically important sedimentary basins.
Keywords: Embagai; Natron; NVH; Olduvai Gorge; Peninj; Tanzania